2019
DOI: 10.21511/ppm.17(3).2019.37
|View full text |Cite
|
Sign up to set email alerts
|

Gain without pain: an international case for a tradable green certificates system to foster renewable energy development in Ukraine

Abstract: This paper elaborates on the theoretical and methodological fundamentals of a tradable green certificates system to foster renewable energy development in Ukraine. It proposes a management mechanism premised on the classical market model of tradable green certificates aiming at increasing the share of electricity from renewable energy sources in the country’s energy mix. Organizational stages of the mechanism formation at the national level and a methodological approach to assess green electricity generation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…The authors of [11][12][13] maintained that the agricultural sector has a considerable potential to produce green energy and implement innovative technologies for that purpose. Based on the comparison and empirical analysis, the authors of [14][15][16][17][18][19][20] identified the instruments for stimulating green energy (feed-in tariff, taxes, green certificates and green investments and bonds) development and proved that efficiency of electricity production technology depends on the country. Lyulyov O. and co-authors [21] maintained that green technologies lower the environmental damage.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [11][12][13] maintained that the agricultural sector has a considerable potential to produce green energy and implement innovative technologies for that purpose. Based on the comparison and empirical analysis, the authors of [14][15][16][17][18][19][20] identified the instruments for stimulating green energy (feed-in tariff, taxes, green certificates and green investments and bonds) development and proved that efficiency of electricity production technology depends on the country. Lyulyov O. and co-authors [21] maintained that green technologies lower the environmental damage.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2022, hydropower, solar, and wind energy plants provided nearly 85% of all renewable electricity production. A significant increase in renewable electricity production will specifically require bioenergy that has considerable potential and can significantly contribute to achieving that goal (Kurbatova et al, 2019;Kurbatova et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, the obtained results showed the scarcity of publications devoted to investigating the impact of determinants of democracy and globalisation processes on renewable energy development [27][28][29][30][31][32][33]. In turn, Fig.…”
Section: Introductionmentioning
confidence: 99%